Linking farmers to futures market in India - Tirtha Chatterjee; Raghav Raghunathan; Ashok Gulati (Indian Council for Research on International Economic Relations (ICRIER), 2019)
Farmers, especially small and marginal, do not directly trade in agri-futures market in India. Their small size, lack of trust and understanding of futures market and dependence on middlemen, are some of the main deterrents. The role of Farmer Producer Organizations (FPOs) is crucial in this context since they can procure commodities, aggregate them and ensure that size and quality standards required for agri-futures trade are met. In her Budget speech for Union Budget of FY20, the Union Finance Minister has set a target of creating 10,000 FPOs in the next five years (by 2024). NABARD has already been in this process of creating FPOs for the last few years (already has more than 3000 FPOs) and the major responsibility of scaling them with 10,000 new ones, is likely to fall on NABARD. Interestingly, NCDEX has also been trying to deepen FPOs participation in markets for the last few years. However, as our analysis shows that between April 2016 and May 2018 only a tiny fraction (0.004 percent) of overall agri-futures trade at NCDEX was through FPOs. This reflects the need for gigantic steps, if FPOs have to be involved in futures trading at any reasonable scale. The need is even greater if one considers the dire necessity of having forward looking cropping patterns, where farmers' planting decisions are based on future prices rather than last year's or even earlier year's prices. Keeping this in mind, the paper identifies the constraints in first linking farmers to FPOs and second, FPOs to futures market. Based on this research about constraints, the paper puts forward a few suggestions for the FPOs, NCDEX, as well as the government for better results: (1) Both FPOs and NCDEX need to focus initially on commodities not pereceived by the Government as 'sensitive' from food security point of view so that minimum disruption takes place in futures markets. This will help them gain confidence in the functioning of futures markets; (2) NCDEX needs to identify production centres, build delivery centres around them and encourage futures trading in these areas; (3) Resource Institutions involved in educating and hand-holding FPOs in futures trading, themselves need to upgrade their knowledge and skills about functioning of futures trading. Government policy and NCDEX both can help them in this direction; (4) Government initiatives like that of Bihar and Rajasthan can help scaling the efforts of linking FPOs to futures markets in other regions, (5) There could also be learning from small holder dominated agriculture of China, that has provided state support in linking farmers to futures, and helped customized products and reduce price distortions, (6) Government's trading arms can also be encouraged to directly participate in the futures market to give confidence to many others, including FPOs; and (7) Instruments like forwards and options have to be encouraged to invite greater participation by FPOs.
Keywords: G4; G10; Q14; Q13; Q18; 330; agri-commodity futures; farmers; farmer producer organizations (FPOs)